Virtual Screening on Indonesian Herbal Compounds as SARS-CoV-2 Spike (S2) Glycoprotein Inhibitors: Pharmacophore Modelling & Molecular Docking Approaches - Sugito, Syailendra Karuna; Cristina, Artha Uli; Harimurti, Putri Saskia; Cendani, Gabriella Regita; Insani, Fauzi Azhar; Erlina, Linda; Paramita, Rafika Indah; Fadilah, Fadilah (Indonesian Journal of Medical Chemistry and Bioinformatics, 2023)
Background: There are still no specific treatments for coronavirus disease (COVID-19) until present days. Several studies have been conducted to determine whether herbal medicine can be an option to be used as a definitive medicine for COVID-19. S2 subunit of spike protein which is responsible for SARS-CoV-2 entry to the host cell, is a potential drug target to inhibit the viral infection. In this study, we aimed to find some compounds from the HerbalDB database that have potential as SARS-CoV-2 spike (S2) glycoprotein inhibitor. Methods: The 6LXT protein was used as the target protein. The procedure in this study consisted of these following steps: protein and ligand preparation, pharmacophore modelling and compound screening, molecular docking, ADME, and toxicity analysis. The docking of hit compounds to the target protein were compared to arbidol and quercetin as positive controls. Results: Four hit compounds were screened from HerbalDB compounds. Two of them, octopamine and L-noradrenaline, showed lower binding energies (respectively, -5.19 and -4.98 kcal/mol) than positive controls whereas the other two compounds, mimosine and L-theanine, showed higher binding energies (respectively, -3.99 and -3.62 kcal/mol) compared to positive controls. Mimosine, L-noradrenaline, octopamine, and L-theanine had toxicity classes of IV, II, IV, and IV, respectively. Conclusion: Octopamine shows the best potential as SARS-CoV-2 spike (S2) glycoprotein inhibitor. However, this compound also poses several toxicity risks and therefore, needs a more elaborate considera-tion upon using. There are still no specific treatments for coronavirus disease (COVID-19) until present days. Several studies have been conducted to determine whether herbal medicine can be an option to be used as a definitive medicine for COVID-19. S2 subunit of spike protein which is responsible for SARS-CoV-2 entry to the host cell, is a potential drug target to inhibit the viral infection. In this study, we aimed to find some compounds from the HerbalDB database that have potential as SARS-CoV-2 spike (S2) glycoprotein inhibitor.